2016
DOI: 10.3390/vaccines4040047
|View full text |Cite
|
Sign up to set email alerts
|

Co-Administration of Lipid Nanoparticles and Sub-Unit Vaccine Antigens Is Required for Increase in Antigen-Specific Immune Responses in Mice

Abstract: A vast body of evidence suggests that nanoparticles function as potent immune-modulatory agents. We have previously shown that Merck proprietary Lipid NanoParticles (LNPs) markedly boost B-cell and T-cell responses to sub-unit vaccine antigens in mice. To further evaluate the specifics of vaccine delivery and dosing regimens in vivo, we performed immunogenicity studies in BALB/c and C57BL/6 mice using two model antigens, Hepatitis B Surface Antigen (HBsAg) and Ovalbumin (OVA), respectively. To assess the requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 35 publications
(43 reference statements)
1
7
0
Order By: Relevance
“…In addition, we demonstrated that SV plus LNP can protect against influenza virus challenge as efficiently as SV plus alum ( Figure 5 ), suggesting the usefulness of the LNP as an adjuvant for influenza vaccines. Our results support those of other recent studies that have highlighted the effectiveness of LNPs as vaccine adjuvants [ 23 , 24 , 25 ]. However, it is not clear whether our LNP can be used with other types of antigens because it does not enhance antigen-specific antibody responses and T-cell responses when rHA is used as an antigen ( Figure 6 and Figure 7 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, we demonstrated that SV plus LNP can protect against influenza virus challenge as efficiently as SV plus alum ( Figure 5 ), suggesting the usefulness of the LNP as an adjuvant for influenza vaccines. Our results support those of other recent studies that have highlighted the effectiveness of LNPs as vaccine adjuvants [ 23 , 24 , 25 ]. However, it is not clear whether our LNP can be used with other types of antigens because it does not enhance antigen-specific antibody responses and T-cell responses when rHA is used as an antigen ( Figure 6 and Figure 7 ).…”
Section: Discussionsupporting
confidence: 92%
“…For vaccine application, LNPs containing mRNA coding for protein antigens have been used to induce strong immune responses, such as antigen-specific antibody responses and T-cell responses in mice and rhesus macaques [ 18 , 19 ]. In addition, there is increasing evidence of the usefulness of LNPs as efficient antigen-delivery vehicles [ 20 , 21 , 22 , 23 , 24 , 25 ]. For example, by using protein antigens from dengue virus and hepatitis B virus, it has been shown that specific LNPs can enhance co-administered antigen-specific antibody responses, CD4 + T-cell responses, and CD8 + T-cell responses in mice, guinea pigs, and non-human primates without the addition of immunomodulatory adjuvant molecules [ 23 , 24 , 25 ], although the precise mechanism of adjuvanticity of specific LNPs remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…When examining the effect of combining LNPs and aluminum in a single formulation, they observed an enhanced B-cell response but a reduced T-cell response. 114 Similar studies by Swaminathan et al demonstrated that LNPs coadministered with a synthetic TLR9 agonist, immune-modulatory oligonucleotides, IMO-2125 (IMO), significantly enhanced immune responses to HBsAg and OVA in comparison to IMO alone. 115 Previous work by Yanasarn et al showed that protein antigens admixed with DOPA-based negatively charged liposomes induced strong, functional antibody responses.…”
Section: Combinatorial Adjuvant Strategiesmentioning
confidence: 99%
“…For instance, De Gregorio et al reported that the adjuvant effect was often lost when the antigen and alum were administered at separate locations [71]. Thoryk et al demonstrated that lipid nanoparticles (LNPs) must be coadministered with antigens to exert adjuvant property [72]. However, Rivera et al observed that ginseng improved antibody response to porcine parvovirus (PPV) antigen regardless of that the ginseng and antigen were coinjected or not [73].…”
Section: Discussionmentioning
confidence: 99%